Development of Mini Virtual Aquatic Ecosystem Learning Media Assisted by Professional 3D Pageflip Software - Arifin, Ahmad Aris (Balai Publikasi Indonesia, 2024)
This development aims to produce a mini virtual learning media product for aquatic ecosystems assisted by professional 3D pageflip software. The development research model used is the Four-D (4D) model, which consists of 4 stages including: (1) define stage, (2) design stage, (3) develop stage, practicality testing is carried out. , and the dissemination stage was not carried out due to time constraints. The trial subjects in this research involved 36 students of SMAN 9 Mataram class X1, and involved teachers as user practitioners and observers to assess the implementation of learning. The data collection techniques used consisted of learning implementation questionnaire sheets, teacher response questionnaire sheets and student responses. The data analysis used is quantitative and qualitative. Based on the results of the practicality test, it can be concluded that the virtual aquatic ecosystem mini media is very practical to use. The teacher's response showed a percentage of 89.32 in the very practical category, and the student response showed a percentage of 86.04 in the very practical category. Meanwhile, learning implementation is 90%, and non-implementation is 10%.